Peptostreptococcus anaerobius: Pathogenicity, identification, and antimicrobial susceptibility. Review of monobacterial infections and addition of a case of urinary tract infection directly identified from a urine sample by MALDI-TOF MS. (December 2021) - Legaria, M.C.; Nastro, M.; Camporro, J.; Heger, F.; Barberis, C.; Stecher, D.; Rodriguez, C.H.; Vay, C.A.
Abstract: Peptostreptococcus anaerobius is a gram-positive anaerobic coccus (GPAC) found in the gastrointestinal and vaginal microbiota. The organism is mainly found in polymicrobial and scarcely in monobacterial infections such as prosthetic and native endocarditis. Anaerobic bacteria have rarely been reported as the cause of urinary tract infection (UTI). Although GPAC are susceptible to most antimicrobials used against anaerobic infections, P. anaerobius has shown to be more resistant. Herein, we report a case of UTI caused by P. anaerobius from a 62-year-old man with a history of urological disease. Surprisingly, the microorganism was directly identified by Matrix-Assisted Laser Desorption-Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) from the urine sample. The isolate was successfully identified by phenotypic methods, MALDI-TOF MS, and 16S rRNA gene sequencing. P. anaerobius showed no β-lactamase-producing activity, was resistant to penicillin, ampicillin, ciprofloxacin and levofloxacin, and displayed intermediate susceptibility to ampicillin-sulbactam and amoxicillin-clavulanic acid. Successful treatment was achieved with oral amoxicillin-clavulanic acid. Antimicrobial susceptibility testing (AST) should be performed on P. anaerobius isolates due to their unpredictable AST patterns and because empirically administered antimicrobial agents may not be active. This report shows that MALDI-TOF MS, directly used in urine specimens, may be a quick option to diagnose UTI caused by P. anaerobius or other anaerobic bacteria. This review is a compilation of monobacterial infections caused by P. anaerobius published in the literature, their pathogenicity, identification, and data about the antimicrobial susceptibility of P. anaerobius . Highlights: Peptostreptococcus anaerobius is a rare cause of monobacterial infections. These monobacterial P. anaerobius infections may occur at variable sites. P. anaerobius was directly identified from a urine sample by MALDI-TOF MS. The monobacterial P. anaerobius infections and the role of anaerobes in UTI has been reviewed. Resistance determination should be carried out in such cases.